Application of Integral Health Index in Evaluation of Efficiency of Rehabilitation of Children with Obesity; Society 5.0: Human-Centered Society Challenges and Solutions; Vol. 416 : Studies in Systems, Decision and Control (SSDC) - Berestneva O. G. Olga Grigorievna (2022, 2022)
Title screen